Deep Ecology Philosophy and Biodiversity Conservation in Nigeria’s Niger Delta - Ikeke, Mark Omorovie (European Journal of Sustainable Development, 2020)
Biodiversity refers to the varieties, multiplicity, and diversity of life in the ecosystem. It is being lost on a daily basis in Nigeria’s Niger Delta. This is as a result of the environmental degradation caused by oil exploration and gas activities. In the process of drilling for oil and exploring for gas resources, the natural environment such as plants, animals and their communities is destroyed and endangered. Oil exploration activities continue unabated in the Niger Delta. There is need to combat biodiversity loss if not many of the benefits from biodiversity will be lost. With critical analysis the philosophy of deep ecology is examined and presented as having potentials to contribute to conserving biodiversity in Nigeria’s Niger Delta. The paper concludes that there is vital need to preserve biodiversity using deep ecology values. Keywords: Deep ecology, biodiversity, conservation, Niger Delta, Nigeria, and Philosophy